2014
DOI: 10.1126/science.1250127
|View full text |Cite
|
Sign up to set email alerts
|

SMN2 splicing modifiers improve motor function and longevity in mice with spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a genetic disease caused by mutation or deletion of the survival of motor neuron 1 (SMN1) gene. A paralogous gene in humans, SMN2, produces low, insufficient levels of functional SMN protein due to alternative splicing that truncates the transcript. The decreased levels of SMN protein lead to progressive neuromuscular degeneration and high rates of mortality. Through chemical screening and optimization, we identified orally available small molecules that shift the balance of SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
428
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(454 citation statements)
references
References 57 publications
19
428
1
6
Order By: Relevance
“…Efficacy testing of SMA therapies has been primarily restricted to mouse models with very low levels of SMN, such as the Δ7 mouse, and is referred to as one of the "severe models," with a median survival of 12-14 d after birth (6)(7)(8)(9)(10)(11)(12). Attempts to generate a robust intermediate model have resulted in mice with near-normal life spans and little to no neuromuscular phenotype (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy testing of SMA therapies has been primarily restricted to mouse models with very low levels of SMN, such as the Δ7 mouse, and is referred to as one of the "severe models," with a median survival of 12-14 d after birth (6)(7)(8)(9)(10)(11)(12). Attempts to generate a robust intermediate model have resulted in mice with near-normal life spans and little to no neuromuscular phenotype (13,14).…”
mentioning
confidence: 99%
“…Among these is the narrow window for testing therapeutic interventions, as the short overall survival time of these mice limits the study of postonset interventions (11,(15)(16)(17). In these severe SMA mice, several studies have demonstrated that successful intervention in the disease course is limited to the early postnatal days (PNDs) (10,17,18). Whether this observation holds true in milder models of SMA remains to be answered but is a critical question, as type II/III patients represent the majority currently awaiting treatment.…”
mentioning
confidence: 99%
“…Badania podstawowe wykazały selektywny wpływ cząsteczek na zwiększenie syntezy białka SMN w hodowli komórkowej. W modelu mysim SMA czą-steczki te wykazały dobrą biodostępność, a przede wszystkim pozytywny wpływ na przeżycie i funkcję ruchową zwierząt [40]. Aktualnie trwa rekrutacja do trzech badań klinicznych cząsteczki RG7916, w tym badania fazy 2 Firefish (ClinicalTrials.gov Identifier: NCT02913482) i Sunfish (NCT02908685) oceniające skuteczność i bezpieczeństwo odpowiednio u pacjentów z SMA1 i MSA2-3.…”
Section: Próby Terapeutyczneunclassified
“…Interestingly, a recent paper reports novel smSMs developed for survival motor neuron splicing and treatment of spinal muscular atrophy. 68 The compounds resulted from a screen using a splicing reporter that followed the endogenous splicing event. RNAseq was performed to inquire specificity.…”
Section: Manipulation Of As As a Potential Therapeutic Avenue In Ckdmentioning
confidence: 99%